Weldability of duplex stainless steels with and without Cu/Ni interlayer using plasma arc welding - Kirik, Ihsan; Ozdemir, Niyazi; Gulumser, Mehmet; Balalan, Zulkuf (Carl Hanser Verlag, 2016)
The aim of this study is to investigate the effect of a monel/nickel interlayer electrode prepared with a thickness of 2 mm on the weldability properties of duplex stainless steel plates welded by means of plasma transfer arc welding. After welding, scanning electron microscopy, X-ray diffraction and energy dispersive spectrometry were carried out to determine the microstructural changes that occurred in the interface regions of the welds. Moreover, tensile strength, microhardness and fractography tests were conducted for assessing the mechanical properties of the welded specimens. The results of tests and examinations indicated that the tensile strength of welded parts with a nickel interlayer was higher than that of with and without a monel interlayer.
Keywords: Plasma arc welding; monel and nickel; nterlayer; duplex stainless steel